PENGUATAN POSISI BADAN PENYELESAIAN SENGKETA KONSUMEN TERHADAP TUGAS PENGAWASAN KLAUSULA BAKU - Evita Amung Kasih, (2023)
The Consumer Dispute Settlement Body (BPSK) is a government institution created as an alternative to out-of-court consumer dispute resolution at a lower cost than the court so as not to burden consumers when seeking justice. BPSK as a consumer dispute resolution institution is not only tasked with resolving consumer disputes but has another duty, namely to supervise standard agreements to ensure that the standard clauses contained therein do not violate Law Number 8 Year 1999 on Consumer Protection. The supervision of standard clauses conducted by BPSK should be active to prevent violations and ensure that business actors contain standard clauses that are in accordance with the Consumer Protection Law. However, in practice, the supervision of standard clauses has not been carried out actively and is still passive. Not only that, the education of standard clause parties has not been intensively carried out so that there are still consumers who do not understand about standard clauses and their rights. The supervision of standard clauses conducted by BPSK has not been running actively due to several issues originating from inside and outside BPSK that need to be reviewed and improved to make BPSK's performance better and to carry out its duties. These existing problems make it difficult for BPSK to carry out its duties, especially the supervision of standard clauses. The non implementation of clause supervision makes it difficult for consumers because business actors can freely contain standard clauses without any supervision which further corners the position of consumers. Therefore, it is necessary to review the problems faced by BPSK, especially since these problems have been going on for a long time and have not found a bright spot that resolves them properly.